CFD Simulation Of The Influence Of Humidity On Explosive Behaviour of Aluminium Nanoparticle - Lee , Weng Soon (IRC, 2016)
In current situation, there are so many researches being carried to identify the explosiveness characteristic of nanomaterials but the researchers concentrated on the size of particle as their main factor for the explosiveness characteristic. In fact, there are plenty other factors which can contribute to the explosiveness characteristic of the nanomaterials that had yet to be research thoroughly which include humidity, the shape of the nanoparticle and others.